ENZYMATIC ACTIVITY OF LACTIC ACID BACTERIA ISOLATES FROM THE GASTROINTESTINAL TRACT OF NILE TILAPIA (Oreochromis niloticus) FROM LAKE RANAU, WEST LAMPUNG AS PROBIOTIC CANDIDATES - Hilma Putri Fidyandini; Rika Iwan Syahputri; Agus Setyawan; Limin Santoso (Universitas Mataram, 2026)
Tilapia (Oreochromis niloticus) cultivated in Lake Ranau, West Lampung, possesses several superior characteristics, including good growth performance, thick flesh, savory taste, and the absence of muddy odor. These advantages are presumed to be associated with the presence of gut microbiota, particularly lactic acid bacteria (LAB), which have potential as probiotics. This study aimed to obtain lactic acid bacteria isolates from the gastrointestinal tract of tilapia, evaluate their enzymatic activities, and determine potential probiotic candidates. The research employed an exploratory method through bacterial isolation, LAB screening using de Man Rogosa Sharpe Agar (MRSA), enzymatic activity assays, morphological and biochemical identification, and molecular analysis based on 16S rDNA sequencing. The results showed that 12 bacterial isolates were successfully grown on MRSA medium. Ten isolates exhibited amylase activity, while all isolates demonstrated lipase and protease activities, indicated by the formation of clear zones around the bacterial colonies. Isolate UNR.11 showed the highest enzymatic activities with clear zone diameters of 25.5 ± 2.80 mm for amylase, 20.4 ± 1.2 mm for lipase, and 22.7 ± 4.06 mm for protease activity. Based on macroscopic, microscopic, biochemical, and 16S rDNA sequence analyses, isolate UNR.11 was identified as Bacillus cereus with 99% similarity. This isolate has potential as a probiotic candidate due to its ability to produce digestive enzymes, namely amylase, lipase, and protease, which may support digestion and nutrient utilization in fish.